Kamisama Kiss. Vol. 8 - Suzuki, Julietta; Kimura, Tomo (Shojo beat manga., 2012)
"Things at the kami convention in Izumo aren't going so well. Nanami tried to earn some respect by guarding death's door while the keeper went off to party. But now she's stuck in the land of the dead, and the residents seem to have a taste for new kami!"--Publisher's web site.